A Study on Impact of Earnings per Share, Dividend per Share Price Earning Ratio on Behaviour of Share Market Price Movements (Pharma Sector) with Special Reference to NSE - H. S. Sridhar; D. Anupama Sundar (Current Overview on Science and Technology Research Vol. 10, 2022)
The focal point of the investigation was to examine the effect of earnings per share, profit per share, and cost-profit proportion. The analysis determined the extent to which Profit per Share, Profit per Share, and Cost Profit Proportion could be used as crucial illustrative variables for forecasting share showcase costs. The analysis has laid down emphasis on the impact of profit per share, profit per share, and cost profit proportion on the share price of the businesses that were considered for the study. The estimation of the quality of factor affiliation has also been investigated. Various websites were used to get the data for the analysis. The companies selected for consideration are those that are listed and actively traded with high volume on the NSE. The details were fetched from five companies in 1 instance (2011-2020). It is evident that diverse factors are significantly required for different market conditions. The research emphasizes on the factors that have an impact on stock costs.